Ultrafast electric field controlled spin correlations in the Hubbard model - Dasari, Nagamalleswara Rao; Eckstein, Martin (Physical Review B, 2019)
Highly intense electric field pulses can move the electronic momentum occupation in correlated metals over large portions of the Brillouin zone, leading to phenomena such as dynamic Bloch oscillations. Using the nonequilibrium fluctuation-exchange approximation for the two-dimensional Hubbard model, we study how such nonthermal electron distributions drive collective spin and charge fluctuations. Suitable pulses can induce a highly anisotropic modification of the occupied momenta, and the corresponding spin dynamics results in a transient change from antiferromagnetic to anisotropic ferromagnetic correlations. To good approximation this behavior is understood in terms of an instantaneous response of the spin correlations to the single-particle properties.
CRIS-Team WoS Importer:2019-10-18